Sub-wavelength lateral detection of tissue-approximating masses using an ultrasonic metamaterial lens - Ezekiel L. Walker (Nature Portfolio, 2020)
Traditional methods for ultrasound detection in biomedical application suffer from limited lateral resolution. Here, the authors show that a phononic metamaterial lens can be used for spatial characterisation of subwavelength objects, even beyond the Fresnel zone of the emitting transducer.